2023
DOI: 10.3389/fnhum.2023.1076873
|View full text |Cite
|
Sign up to set email alerts
|

Structural differences among children, adolescents, and adults with attention-deficit/hyperactivity disorder and abnormal Granger causality of the right pallidum and whole-brain

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a childhood mental health disorder that often persists to adulthood and is characterized by inattentive, hyperactive, or impulsive behaviors. This study investigated structural and effective connectivity differences through voxel-based morphometry (VBM) and Granger causality analysis (GCA) across child, adolescent, and adult ADHD patients. Structural and functional MRI data consisting of 35 children (8.64 ± 0.81 years), 40 adolescents (14.11 ± 1.83 years), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…This study investigated possible patterns of directional influence between the cortex and striatum in children and adolescents with ADHD by using the GCA, a commonly used causal method. Agoalikum and colleagues found a mutual influence between the striatum and cortex in ADHD 36 . To further refine this influence pattern, we employed a detailed striatum VII‐subregions segmentation atlas in the current study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This study investigated possible patterns of directional influence between the cortex and striatum in children and adolescents with ADHD by using the GCA, a commonly used causal method. Agoalikum and colleagues found a mutual influence between the striatum and cortex in ADHD 36 . To further refine this influence pattern, we employed a detailed striatum VII‐subregions segmentation atlas in the current study.…”
Section: Discussionmentioning
confidence: 88%
“…Agoalikum and colleagues found a mutual influence between the striatum and cortex in ADHD. 36 To further refine this influence pattern, we employed a detailed striatum VII-subregions segmentation atlas in the current study. We found altered GCA connectivity in the VIS-striatum-DMN pathway exhibited the interaction effects between diagnosis and age and the closed relationships with clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…We found that some brain regions in ADHD patients have changed in the way information interacts. Specifically, the function of the bilateral thalamus to receive information was decreased, which may be caused by changes in the volume of the thalamus in ADHD patients [ 23 , 75 ]. The thalamus is a key subcortical structure of the cortico-stria-to-thalamo-cortical loop (CSTC) [ 76 ], mostly involved in attention and cognitive behavioral processes, and is considered a mediator connecting the basal ganglia, cerebral cortex, and cerebellum [ 47 , 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing this to undirected functional networks, direction increases our understanding of the association between brain function and behavior [ 20 ]. Some studies have confirmed the abnormal effective connectivity of certain brain regions and the directional causal relationships among ROIs in ADHD patients, which could differentiate patients with ADHD from NC [ 21 , 22 , 23 , 24 ]. However, the majority of these studies have described macro- and micro-scale network properties in functional networks in these individuals, and the underlying meso-scale characteristics of brain function networks in ADHD patients are not well known.…”
Section: Introductionmentioning
confidence: 99%